2018
DOI: 10.1039/c8nr05734f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity in percolating nanocomposites: a molecular dynamics investigation

Abstract: In this work we present a molecular dynamics investigation of thermal transport in a silica-gallium nitride nanocomposite. A surprising enhancement of the thermal conductivity for crystalline volume fractions larger than 5% is found, which cannot be predicted by an effective medium approach, not even including percolation effects, the model systematically leading to an underestimation of the effective thermal conductivity. The behavior can instead be reproduced if an effective volume fraction twice larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…The behaviour can be perfectly reproduced with an effective medium model, assuming for the fully nano-crystalline sample a thermal conductivity of 4 W/mK, as found in Ref 41 for a grain size of 5 nm, and for the amorphous phase k T = 1.5 W/mK. Our result is thus quite different from the case of nanocrystalline inclusions of GaN embedded in amorphous SiO 2 , where an enhanced percolation was found 15 . More intriguing is the elastic contrast dependence: surprisingly, we don't see any effect of the elastic contrast within our error bars, although we have shown that the vibrational dynamics much depends on it.…”
Section: Thermal Conductivitysupporting
confidence: 53%
See 1 more Smart Citation
“…The behaviour can be perfectly reproduced with an effective medium model, assuming for the fully nano-crystalline sample a thermal conductivity of 4 W/mK, as found in Ref 41 for a grain size of 5 nm, and for the amorphous phase k T = 1.5 W/mK. Our result is thus quite different from the case of nanocrystalline inclusions of GaN embedded in amorphous SiO 2 , where an enhanced percolation was found 15 . More intriguing is the elastic contrast dependence: surprisingly, we don't see any effect of the elastic contrast within our error bars, although we have shown that the vibrational dynamics much depends on it.…”
Section: Thermal Conductivitysupporting
confidence: 53%
“…Indeed, it has been recently reported that no remarkable effect could be observed in thermal and electric transport properties in a nanocomposite when the elastic and electric properties of the crystalline inclusions are too similar to the ones of the matrix 14 . When the elastic contrast is significant, instead, contradictory results have been reported, such as a strong thermal conductivity reduction, as measured in composites made of Si nanocrystals embedded in a polystyrene matrix 9 or its enhancement beyond normal percolation as simulated in glassy silica with embedded nanocrystalline inclusions of GaN, both results being at odds with all effective medium predictions 15 . It is thus still not understood how the elastic contrast acts on thermal transport in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Different parameters have different effects: the rigidity contrast impacts the scattering and eventually pins the energy [ 12 ]. A higher surface to volume ratio is known to decrease the effective thermal conductivity [ 13 ]. Less instinctively, it has been shown in the same study that the relative crystalline orientation between the particles also modifies the thermal conductivity of the material, banning or promoting the phonon percolation.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the nanoscale, the intrinsic properties of the materials can change, for instance with their size [ 17 ]. These variations render the predictions based on the bulk properties difficult; for instance, in the case of orientation [ 13 ], the effective medium approach proposed [ 18 ] fails and the microstructure has to be explicitly considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation